Zagotavljanje spoštovanja človekovih pravic pri delovanju gospodarskih subjektov s sklenitvijo pogodbe - Čertanec, Ana (Podjetje in delo, 2015)
The author theoretically discusses the issue of respecting the human rights in the operation of businesss entities. Since business entities are not yet legally required to respect human rights, the most important issue that arises is how to ensure that the business entities will indeed respect human rights. One of the options at hand is conclusion of a contract that would include a special provision on obligation to respect human rights and a sanction when such obligation is breached. Currently, this option is the best way to ensure that for any violation of human rights business entities are appropriately sanctioned. It is clear that without proper sanctions respecting the human rights in the operation of business entities is hard to guarantee.
Keywords: človekove pravice; gospodarske družbe; human rights; pogodbe; spoštovanje